Vacant Urban Spaces: Definitions, Challenges and Perspectives in Urban Regeneration - Amine Mseddi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
Through the dynamic process of cities evolution, vacant spaces tend to appear. Certainly, empty and abandoned lots in a dense urban fabric could persists for numerous reasons. This phenomenon could be perceived from different perspectives from urbanists, and landscapers to architects, geographers, environmentalists and sociologists. Multiple data, parameters and definitions are in play. This multidisciplinarity produces an issue of terminology in the scientific body related to urbanism and landscape architecture. More academic clarity is needed to have more efficiency concerning the perspectives of vacant spaces. This paper is presenting a scope of definitions of urban vacant spaces. It is based on the works of Roger Trancik, Merten Nefs among other researchers. This literature review aims to discern these definitions, in the process of establishing the role of the vacant urban spaces as a sustainable way of urban regeneration, illustrated by some examples showing considerable transformations of unused empty areas.